Preliminary Investigation of the Mechanical Anisotropy of the Normal Human Corneal Stroma - Chao Xue; Yaoqi Xiang; Min Shen; Di Wu; Yan Wang (Journal of Ophthalmology)
Purpose. To investigate the anisotropic characteristics of the normal human corneal stroma using fresh corneal tissue. Methods. Sixty-four corneal specimens extracted from stromal lenticules were included in this study. The specimens were cut in the temporal-nasal (horizontal) or superior-inferior (vertical) direction. Strip specimens were subjected to uniaxial tensile testing. The tensile properties of the specimens were measured and compared in the two directions. Results. The low-strain tangent modulus was statistically significantly greater in the vertical direction than in the horizontal direction (1.32 ± 0.50 MPa vs 1.17 ± 0.43 MPa; P=0.035), as was the high-strain tangent modulus (51.26 ± 8.23 MPa vs 43.59 ± 7.96 MPa; P≤0.001). The elastic modulus in the vertical direction was also higher than that in horizontal direction at stresses of 0.01, 0.02, and 0.03 MPa, but not statistically significant; so, P=0.338, 0.373, and 0.417, respectively. Conclusions. The biomechanical behavior in normal human corneal stroma tissue is slightly stiffer in the vertical direction than in the horizontal direction. This information may aid our understanding of the biomechanical properties of the cornea and related diseases.